"E foi um deus nos acuda": migrações, urbanização e luta de classes na terra de Lucas. 1977-1990. - Silva, Valter Zaqueu Santos da (2015)
This dissertation had as its object the process of urbanization of the city of Feira de Santana and the struggles of the working class for better conditions of life, so we focused on conflicts over urban bus service between 1977 and 1990. We note that the struggles for shuttle service there were not dissociated from other struggles for housing, paving, sanitation, garbage collection, street lighting, piped water and access to education, contradictions arising from the industrial urbanization process that submitted local workers. This phenomenon has intensified the class struggle in the city and interfered in the projects and in the sense given to the city uses. During the second half of the twentieth century, in Brazil there was an intense migratory flow towards rural town, to get around town these workers had to adapt to urban life and face problems hitherto new, While workers were subordinate aggregate form the urban environment they too, resisted subordination and have demanded that their needs also to be part of the agenda, in turn, the ruling class insisted on streamlining the city space and drive downtown workers and their traditional forms of socialization .